Analisis kadar paracetamol pada darah dan serum SIS KADAR PARACETAMOL PADA DARAH DAN SERUM: Analysis of paracetamol levels in blood and serum - Sudarma, Nyoman; Subhaktiyasa, I Putu Gede (Bali Medika Jurnal, 2021)
Paracetamol is a group of analgesics that is pain relief in the way of work and inhibits the synthesis of prostaglandins especially in the central nervous system. Paracetamol given orally will be absorbed quickly and reach peak serum levels within 30-120 minutes. The purpose of this research is to determine the level of paracetamol in blood and serum. The sample used were blood and serum samples from respondents who consumed the 500 mg paracetamol drug. Blood samples were taken 2 hours after consuming the drug paracetamol. To get serum, blood must be centrifuged, with the process of centrifugation of confounding substances in the blood can be minimized. Qualitative analysis of paracetamol levels in blood and serum was analyzed using gas chromatography-mass spectrometry (GC-MS). Paracetamol extraction on blood and serum samples using the Solid Phase Extraction (SPE) method. The extraction results were derivatized using BSTFA containing 1% TMCS and analyzed using gas chromatography-mass spectrometry (GC-MS). Quantitative analysis was performed by calculating paracetamol levels using the equation of the regression line y = 50207x + 56321. The results of this research showed that blood and serum samples showed positive paracetamol at 15,056 and 15,101 retention times. The level of paracetamol in blood samples was 175,2 ppm and the level of paracetamol in serum samples was 56,7 ppm.